Diseño de un producto turístico de sol y playa que contribuya al desarrollo del cantón San Vicente - Bravo Mendoza, Mirna Alejandra (2015)
The main objective of this research was to design a tourism product of sun and sand for the development of the county. The theoretical framework was developed to support the object of study, the methodology used corresponds to a scientific, descriptive study and the techniques were field research and scientific observation. For this study it was necessary to make a situational diagnosis that allowed delimiting the area of study, the current situation of commodities and infrastructure, the economic and socio-cultural aspects and determining environmental factors. Together they proceeded to review the inventory of resources, as was a general SWOT analysis of the county, determining the general problem with its stipulated solution and strategy. Through market research surveys where the customer profile was settled, characteristics of the demand and supply position this tourist product for sun and beach is also determined. As a last point of the investigation after the information collected and obtained we proceeded to design a product for tourists based on the requirements that became the starting point for the design of an innovative product, adapted to the needs of both domestic and foreign tourist, with planning where sun and beach tourism and its supplements are promoted, and so in this way contributing to the tourism, economic and social development of the inhabitants of the community of San Vicente who will be the main beneficiaries.